Chaining The Words Activity on Teaching Writing of Affixes on Legal Document: A Morphosyntax Perspective - Paramita Kusumawardhani; Syihabuddin Syihabuddin (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
The research aims to analyze the use of chaining activity on teaching writing of affixes on legal document. Language is used to communicate each other, both written and spoken, to ease the audiences so it can be understood when the first time they read or hear it. On legal document, it should be simplified in written, used appropriate words and sentences structures, and presented clearly and logically. Language is also related to writing, of Morphology and Syntax that is in line with affixes. The right form of writing in Morphosyntax on legal document can ease both the readers and hearers when they have legal problems, so the appropriate actions can be taken. Morphosyntax is the combination of Morphology and Syntax. Morphosyntax studies about how words are formed and combined with structures into a good sentence. The method used was qualitative method to give the understanding about chaining the words in improving the writing skill and connecting the affixes to the base word especially in English legal document. The legal document was used as the research instrument. The participants of the research were the 1st semester of accounting students at University of Bina Sarana Informatika. The result of the research is there are some affixes, as the Morphology aspects, commonly used on the legal document, the affixes are: -ance, -al, -ence, -er, -ing, -ment, -or, etc. For Syntax aspects, there are grammar, noun, verb, adjective, adverb and preposition found on the legal document.